2020
DOI: 10.18203/2394-6040.ijcmph20204383
|View full text |Cite
|
Sign up to set email alerts
|

Preferences, perceptions and barriers to E-learning among medical students during COVID-19 pandemic lockdown in India

Abstract: Background: Following the imposition of the nationwide lockdown on 24th March 2020, many medical institutions adopted E-learning as a method to ensure continuity in medical education. Understanding perceptions and preferences of medical students and addressing their barriers are essential for a seamless learning experience.Methods: Data was collected using a semi-structured online questionnaire after obtaining informed consent. A total of 296 students of the second year MBBS and pre-final year were recruited u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…After the implementation of the lockdown, the number increased to 109 (35.5%). This is similar to a study conducted by Suryawanshi DM et al 16 …”
Section: Discussionsupporting
confidence: 92%
“…After the implementation of the lockdown, the number increased to 109 (35.5%). This is similar to a study conducted by Suryawanshi DM et al 16 …”
Section: Discussionsupporting
confidence: 92%
“…Issues with this approach include screen fatigue and distraction for students and lecturers [ 20 ]. Consequently, surveys from LMICs during the COVID-19 period show that students prefer traditional teaching compared to online teaching [ 21 ], and that comprehension from face-to-face lectures is better than online teaching [ 22 ]. This shows that investment into developing online learning material is important in order to improve student acceptability.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that the utility of e-learning has increased during the COVID-19 pandemic but students preferred e-learning in combination with traditional teaching. Suryawanshi et al, 10 surveyed 286 students of the second year MBBS and pre-final year students where 48.2% students showed preference for blended mode of teaching. A total of 62.9% cited that there is lack of personal interaction with the teacher.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether it's traditional teaching or e-learning, teachers need to be more engaging for better outcomes. [7][8][9][10] Whether it's a traditional way or e-learning, students lose interest if they are unable to comprehend a topic. E-learning does compliment serious learners, but casual learners may find it difficult to get full benefits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation